Cis-β-Ru(II)heteroatom-stabilized-carbene complexes supported by tetradentate Schiff-base salen ligand. (1st May 2021) - Chen, Daqing; Guan, Xiangguo; Wan, Qingyun; Low, Kam-Hung; Huang, Jie-Sheng
Graphical abstract: A panel of stable ruthenium carbene complexes bearing a tetradentate salen ligand, with their carbene-C atom adjacent to heteroatom, were synthesized from cis - β -Ru(II)-bis(CO) complex by reacting with the corresponding carbene precursors. Abstract: A panel of stable ruthenium carbene complexes bearing a tetradentate salen ligand, with their carbene-C atom adjacent to heteroatom, were synthesized from cis - β -Ru(II)-bis(CO) complex by reacting with the corresponding carbene precursors. These carbene complexes, which were fully characterized by elemental analysis, NMR, IR spectroscopy and X-ray-crystal structure determination, all adopt a cis-β configuration; the heteroatom (N or O) adjacent to the carbene C atom contributes to the high stability of these complexes both in solution and in solid state. DFT calculations were also performed to gain insight into the Ru-Ccarbene bonds.